International comparison on Ag|AgCl electrodes for pH measurement. (April 2015) - Brewer, P.J.; Panagoulia, D.; Brown, R.J.C.; Tromans, A.; Reyes, A.; Arce, M.; Vospelova, A.; Roziková, M.; Pratt, K.W.; Asakai, T.; Jakobsen, P.T.; Camões, M.F.; et al.
Graphical abstract: Highlights: First practical international comparison of the characteristics of Ag|AgCl electrodes. Important step towards optimising preparation methods. Factors that influence electrode performance and repeatability. Will improve future international comparability in pH measurement. Abstract: The first practical comparison of the characteristics of Ag|AgCl electrodes prepared at different National Metrology Institutes (NMIs) has been carried out as a pilot study organised by the Consultative Committee for Amount of Substance (CCQM). Each NMI prepared at least three Ag|AgCl electrodes representative of those employed in their primary pH calibration facilities. The electrodes were sent to a coordinating laboratory where comparative measurements of their potential difference to a de facto reference, slope as a function of chloride ion concentration and electrochemical impedance were made. Electrodes from most NMIs were highly repeatable and consistent within the typical rejection criteria applied during production. An analysis of the electrode slopes in a phosphate buffer containing different concentrations of NaCl revealed the influence of variances in the Ag|AgCl electrodes between NMIs on the certified pH value of the buffer solution. The difference between NMIs is consistent with submitted values in CCQM-K9, although biases were smaller in the analysis here, suggesting the presence of other unknown contributions to the uncertainty such as cell design. The smaller biases observed in this work may also reflect improvements in the Ag|AgCl electrodes since CCQM-K9 was performed. Electrochemical impedance spectroscopy suggests a similar microstructure for electrodes prepared by most NMIs.